Efektivitas SECARIC Diary dalam Meningkatkan Self-Care dan Kualitas Hidup Penderita Diabetes Mellitus Tipe 2 - Beta Yusnita Elparida Sitanggang; Agustina Sari; Abdullah Syafei (Pusat Riset dan Inovasi Nasional, 2023)
Diabetes mellitus is a degenerative disease that cannot be cured and has a risk of complications if not adequately controlled. Self-care is an important aspect of managing diabetes mellitus independently to improve the quality of life and well-being of the diabetic. One of the strategies to enhance the self-care management skills of the diabetic is to provide education through the booklet SECARIC Diary. This type of research is a quasi-experimental quantitative study with a pre-test-post-test design with the control group. Sampling was conducted using purposive sampling technique at several Posyandu in Desa Karang Asem Barat with a total sample of 22 respondents for the control group and 22 respondents for the intervention group. Data analysis used paired t-tests on self-care and quality-of-life variables with a p-value of 0.000 at a significance level of α = 0.05. Furthermore, data analysis was performed using an independent t-test with a p-value of 0.000 and a t-count of 4.756 on the self-care management variable and a p-value of 0.042 and a t-count of 2.098 on the quality of life variable. The results showed that the SECARIC Diary booklet media intervention could improve self-care management abilities and quality of life for type 2 diabetes mellitus patients in Desa Karang Asem Barat.